Branch Manager CSR Perceptions of Customer Satisfaction, Trust, and Loyalty - Zachrani, Alifia; Qurrota A'yun, Annisa (Journal Economic Business Innovation, 2025)
Purpose: The purpose of this study is to analyze the impact of branch managers perception of corporate social responsibility (CSR) toward perceptions of customers, and its impact to customer satisfaction, trust, engagement and loyalty in banking service in Indonesia.Methods: A quantitative method was employed using structured questionnaires and statistical analysis to analyze the relationships between CSR perceptions, satisfaction, trust, engagement, and loyalty.Results: The results offer that branch managers positive perceptions regarding CSR play an important role for greater customer perceptions towards CSR. This, in turn, has a positive impact on customer satisfaction, trust, and loyalty.” Using engagement as a mediator between trust and loyalty reflects it as the main link between the two, the life belt of customer-bank relationship.Novelty: This is the first study that examines CSR in banking from the managerial level perspective, and its direct effects on customer attitudes and behaviors. From the basis of both managerial and customer perspectives, it offers an understanding of the relationship between CSR and relationship marketing consequences.Implications: The study reinforces the value of CSR in relation to sustainability of customer relationship. These efforts can bolster trust and loyalty by improving CSR training for branch managers and customizing CSR initiatives to be in alignment with customer values. Future studies may expand these findings to other financial industries or consider the moderating impacts of demographic factors.